2006
DOI: 10.1016/j.tcb.2006.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The role of clathrin-dependent endocytosis in bacterial internalization

Abstract: Internalization of bacteria into mammalian host cells has been studied extensively in the past two decades. These studies have highlighted the amazingly diverse strategies used by bacterial pathogens to induce their entry in non-phagocytic cells. The roles of actin and of the whole cytoskeletal machinery have been investigated in great detail for several invasive organisms, such as Salmonella, Shigella, Yersinia and Listeria. Recent results using Listeria highlight a role for the endocytosis machinery in bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 74 publications
1
106
0
Order By: Relevance
“…40,41 The entry of AIEC LF82 bacteria involves lipid rafts as we observed that CTX B subunit, a drug that binds the GM1 gangliosides known to be clustered in lipid rafts, was recruited and accumulated around AIEC LF82 entering bacteria (Figure 3a). This was confirmed by treatment of macrophages with MbCD, a cholesterol-depleting molecule that induced a 1.9-fold decrease in the number of LF82 bacteria internalized in macrophages (Figure 3b).…”
Section: Inhibition Of Aiec Lf82 Endocytosis Decreased the Numbers Ofmentioning
confidence: 90%
“…40,41 The entry of AIEC LF82 bacteria involves lipid rafts as we observed that CTX B subunit, a drug that binds the GM1 gangliosides known to be clustered in lipid rafts, was recruited and accumulated around AIEC LF82 entering bacteria (Figure 3a). This was confirmed by treatment of macrophages with MbCD, a cholesterol-depleting molecule that induced a 1.9-fold decrease in the number of LF82 bacteria internalized in macrophages (Figure 3b).…”
Section: Inhibition Of Aiec Lf82 Endocytosis Decreased the Numbers Ofmentioning
confidence: 90%
“…3A and B). Clathrin is the major protein component of a major class of coated vesicles and plays an important role in endocytosis (24)(25)(26), a pathway known to be involved in pathogen internalization (27,28). We therefore speculated that COP35 is internalized via a clathrin-dependent endocytic pathway by direct or indirect interaction with CHC in living cells.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane dynamics regulates the internalization of different types of cargos, from small molecules, such as ligand-bound receptors, to large cargoes such as bacteria (Veiga and Cossart, 2006;Zwang and Yarden, 2009). This process is dependent on re-organization of the actin cytoskeleton, which underlies membrane remodelling and assists receptor clustering and signalling (reviewed in Smythe and Ayscough, 2006;McClatchey and Fehon, 2009;Treanor et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To test this possibility we turned to a different bacterium, S. enterica serovar Typhimurium, whose entry does not involve a specific receptor, but is dependent on extensive remodelling to the actin cytoskeleton (Veiga and Cossart, 2006). We ) for the indicated periods of time.…”
Section: Uch-l1 Promotes Invasion Of Epithelial Cells By S Enterica mentioning
confidence: 99%